Tannic acid-imidazole / polyacrylamide composite hydrogel as well as preparation method and application thereof
By preparing tanninic acid-imidazole/polyacrylamide composite hydrogel, the problems of existing antibacterial materials' toxicity, narrow antibacterial spectrum and difficult load release are solved, broad-spectrum antibacterial and efficient antioxidant are achieved, and application potential in multiple fields is demonstrated.
Patent Information
- Application Number
- CN202411796251.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Existing antibacterial materials have problems with toxicity, narrow antibacterial spectrum, and difficult to accurately control the load and release of antibacterial agents, making it difficult to effectively deal with the challenges of antibiotic resistance.
By preparing tannin-imidazole/polyacrylamide composite hydrogel, the antibacterial and antioxidant effects of tannin, imidazole enhances mechanical properties, achieves broad-spectrum antibacterial, and optimizes antibacterial load and controlled release.
It has achieved significant antibacterial effects on Staphylococcus aureus and E. coli, with efficient free radical clearance, and demonstrated its application potential in the fields of biomedicine, packaging and public health.
Smart Images

Figure CN119552324A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of antibacterial materials, and specifically relates to a tannic acid-imidazole / polyacrylamide composite hydrogel and a preparation method and application thereof. Background Art
[0002] Antibiotics are currently the main drugs for treating bacterial infections, but their excessive and improper use has led to serious drug resistance problems, posing a great threat to public health. In order to meet this challenge, researchers are actively exploring the synthesis of compounds with unique antibacterial activity. Antibacterial hydrogels show broad prospects in the treatment of chronic wounds, especially in addressing the challenge of antibiotic resistance (AMR). However, traditional technologies such as silver-based dressings have toxicity problems and a narrow antibacterial spectrum. Although low-temperature plasma-activated hydrogels (PAHT) achieve sterilization and healing through the dual effects of reactive oxygen and nitrogen species (RONS), the loading and release of RONS are difficult to accurately control, limiting their effectiveness.
[0003] At present, tannic acid (TA) hydrogel has been reported to damage the external structure of Candida albicans, and the degree of damage increases with the increase of its concentration. Therefore, how to use tannic acid and imidazole compounds to prepare gel antibacterial materials with good synergistic effects and exert their protective effect on wounds is an important issue in current industrial research. Summary of the invention
[0004] In view of this, the present invention discloses a tannic acid-imidazole / polyacrylamide composite hydrogel and a preparation method and application thereof.
[0005] It should be noted that since tannic acid provides antibacterial and antioxidant effects, imidazole can enhance the mechanical properties and tolerance of the composite hydrogel. The combination of the two achieves broad-spectrum antibacterial properties, while optimizing the antibacterial agent load and controlled release, forming a durable antibacterial barrier, promoting wound healing, and combining high efficiency and biocompatibility, providing an innovative solution for the upgrade of traditional dressings. Therefore, the hydrogel designed based on the tannic acid-imidazole complex provides a new solution for synergistically enhancing antibacterial properties, multifunctional integration, and toxicity management, opening up a new path for chronic wound treatment and antibacterial agent substitution.
[0006] Furthermore, the present invention successfully prepared a tannic acid-imidazole organic complex by directly polymerizing antibacterial units and introduced it into the network structure of the hydrogel. The composite hydrogel material exhibited excellent swelling properties, mechanical stability and significant antibacterial effects on Staphylococcus aureus and Escherichia coli under a variety of conditions, and at the same time had a high free radical scavenging rate, demonstrating its application potential in the fields of biomedicine, packaging and public health.
[0007] Specifically, the tannic acid-imidazole composite polymer forms a stable structure through hydrogen bonding and chemical cross-linking, and its infrared spectrum ( Fig.12 ) characteristics show that: at 3300-3500cm -1 In the range of 1000-1100cm, the absorption peaks of hydroxyl and NH weaken and red-shift, indicating the enhancement of hydrogen bonding; -1 The newly added characteristic peaks are attributed to the formation of ether bonds (COC) and amine bonds (CN). Subsequently, acrylamide initiated a free radical polymerization reaction in situ, and the tannic acid-imidazole composite polymer and polyacrylamide significantly improved the compactness of the gel network through hydrogen bonding of functional groups such as polyphenols and amides. The multi-point chemical cross-linking of the complex provides structural support for the gel, while capturing antimicrobial molecules in the pores, improving its loading capacity and controlled release performance. The honeycomb three-dimensional network of the composite hydrogel effectively improves the porosity and antimicrobial loading capacity.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The first object of the present invention is to provide a method for preparing a tannic acid-imidazole / polyacrylamide composite hydrogel.
[0010] In order to achieve the above object, the present invention adopts the following technical solution:
[0011] A method for preparing a tannic acid-imidazole / polyacrylamide composite hydrogel, the method specifically comprising the following steps:
[0012] (1) dissolving tannic acid in deionized water to obtain a tannic acid solution; then taking a certain mass fraction of the tannic acid solution, adding tannic acid and imidazole in a suitable ratio, and stirring in an ice water bath for a certain period of time;
[0013] (2) adding a certain amount of epichlorohydrin dropwise at a rate of 0.5 mL / min into the reaction system of step (1), continuing the reaction, and after the reaction is completed, centrifuging and freeze-drying to obtain a tannic acid-imidazole composite polymer (TIP);
[0014] (3) The tannic acid-imidazole composite polymer TIP was added to deionized water and heated to dissolve, and acrylamide (AM), ammonium persulfate (APS) and N,N'-methylenebisacrylamide (BIS) were added. After stirring, the mixture was placed in an oven overnight, and APS was used to thermally initiate free radical polymerization to prepare a composite hydrogel.
[0015] Optionally, in step (1), the mass fraction of the tannic acid solution is 0.5% to 30%, the molar ratio of tannic acid to imidazole is 1:1 to 1:20, and the stirring time of the two is 0.5-5h.
[0016] Optionally, in step (2), 0.5-15 mL of epichlorohydrin is added to 50 mL of the mixed solution of tannic acid and imidazole, and the reaction is continued in an ice-water bath for 8-24 hours.
[0017] Optionally, in the step (2), after the reaction is completed, the tannic acid-imidazole composite polymer is centrifuged at a speed of 3000-10000 rpm for 5 min to 1 h, and the tannic acid-imidazole composite polymer is obtained after freeze-drying.
[0018] Optionally, in the step (3), the amount of tannic acid-imidazole composite polymer is 0.01-2 g, the amount of deionized water is 5-100 mL, the amount of acrylamide monomer added is 5 mg-15 g, and after sufficient stirring, 5 mg-1 g of ammonium persulfate and 5 mg-1 g of N,N'-methylenebisacrylamide are added to the solution respectively, and the prepolymer solution is obtained after stirring evenly.
[0019] Furthermore, in the step (3), the temperature of the tannic acid-imidazole / polyacrylamide prepolymer solution placed in the oven is 20° C. to 100° C., and the overnight preparation time is 30 min to 12 h.
[0020] In order to fully disclose the technical points of this case, preferably, the preparation method of the above-mentioned tannic acid-imidazole / polyacrylamide composite hydrogel is as follows:
[0021] Take 50mL of 6% tannic acid aqueous solution, dissolve it in an ice water bath for 1h according to the molar ratio of tannic acid to imidazole of 1:13, then add epichlorohydrin with the same molar number as imidazole, and continue to react for 1.5h to obtain a tannic acid-imidazole composite polymer. The total phenol content is >90% determined by the Folin phenol method; 0.4 of the tannic acid-imidazole composite polymer is dissolved in 20mL of deionized water, and then 7.5g of acrylamide monomer is added. After sufficient stirring, 0.3g of ammonium persulfate and 0.75N,N'-methylenebisacrylamide are added to the solution respectively, and the prepolymer solution is obtained after stirring evenly. The beaker containing the prepolymer solution is placed in a 60℃ oven for 6h to prepare a tannic acid composite imidazole / polyacrylamide composite antibacterial hydrogel.
[0022] The second technical purpose of the present invention is to provide a tannic acid-imidazole / polyacrylamide composite hydrogel prepared by the above method.
[0023] It should be noted that the microstructure of the tannic acid-imidazole / polyacrylamide is a porous structure formed by the tannic acid-imidazole complex and the polyacrylamide, with well-developed pores and imidazole evenly distributed inside the gel. Figure 7 shown.
[0024] It is worth noting that the purpose of the present invention is to solve the problem of increased bacterial resistance caused by the abuse of antibiotics. A new type of antibacterial material is successfully prepared by direct polymerization of antibacterial units. The material not only has a dual antibacterial effect, but also exhibits high chemical stability, better hydrogel performance and a wide range of applications. These characteristics make tannic acid-imidazole / polyacrylamide composite hydrogel have broad application prospects in many fields such as food, packaging and medical treatment, which is of great significance to improving the level of public health and promoting healthy sustainable development.
[0025] The third technical purpose of the present invention is to provide an application of the tannic acid-imidazole / polyacrylamide composite hydrogel as described above in biomedicine, packaging and public health.
[0026] Specifically, the tannic acid-imidazole / polyacrylamide composite hydrogel of the present invention has a significant antibacterial effect on Staphylococcus aureus and Escherichia coli, and the diameter of the antibacterial zone can reach more than 30 mm.
[0027] Escherichia coli and Staphylococcus aureus were inoculated into beef jelly liquid culture medium. After overnight culture, the composite hydrogel was placed in the wells. After 24-48 hours of culture, the bacterial activity was counted by a colony counting / inhibition zone measuring instrument.
[0028] Furthermore, Escherichia coli and Staphylococcus aureus were inoculated into 0-1000 mL beef jelly liquid culture medium, and cultured overnight at 37° C. and 150-1000 r / min in a shaking incubator for later use.
[0029] Furthermore, the Escherichia coli and Staphylococcus aureus bacterial solutions were placed in a constant temperature incubator (37° C., 150 rpm) for shaking culture for 0.5 to 2 hours, and then diluted 10 to 100,000 times with sterile PBS.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The tannic acid-imidazole / polyacrylamide composite hydrogel prepared by the present invention is a bacteriostatic material that has a simple production process and low price and can be used for wound bacteria and fungi.
[0032] 2. The tannic acid-imidazole / polyacrylamide composite hydrogel prepared by the present invention uses imidazole with the simplest structure, and its cost is much lower than other modified imidazole derivatives prepared to improve antibacterial efficiency.
[0033] 3. The tannic acid-imidazole / polyacrylamide composite hydrogel prepared by the present invention has a high compression modulus, the imidazole is evenly distributed in the composite material, the internal pores of the material are well developed, the tannic acid-imidazole composite polymer is not easy to lose, and the antibacterial effect is long-lasting.
[0034] 4. The tannic acid-imidazole / polyacrylamide composite hydrogel provided by the present invention can be used as an antibacterial wound gel, has strong adhesion and self-healing properties, and the antibacterial gel prepared by the invention can not only cover the wound well but also can be used multiple times. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0036] Figure 1 This is a graph showing the antibacterial effect of tannic acid-imidazole / polyacrylamide composite hydrogel on Staphylococcus aureus for 24 hours.
[0037] Figure 2 This is the antibacterial effect of tannic acid-imidazole / polyacrylamide composite hydrogel on Escherichia coli for 24 hours.
[0038] Figure 3 This is a graph showing the antioxidant properties of tannic acid-imidazole / polyacrylamide composite hydrogel against DPPH.
[0039] Figure 4 This is a graph showing the antioxidant properties of tannic acid-imidazole / polyacrylamide composite hydrogel against ABTS.
[0040] Figure 5 This is a diagram of the mechanical properties of tannic acid-imidazole / polyacrylamide composite hydrogel.
[0041] Figure 6 This is the swelling performance diagram of tannic acid-imidazole / polyacrylamide composite hydrogel.
[0042] Figure 7 This is a scanning electron microscope photo of tannic acid-imidazole / polyacrylamide composite hydrogel.
[0043] Figure 8 This is a compression modulus-elongation measurement diagram of tannic acid-imidazole / polyacrylamide composite hydrogel.
[0044] Fig. 9 This is a compression modulus-time measurement graph of tannic acid-imidazole / polyacrylamide composite hydrogel.
[0045] Fig.10 This is the compression modulus-temperature measurement graph of tannic acid-imidazole / polyacrylamide composite hydrogel.
[0046] Fig.11 This is the compression modulus-angular velocity measurement diagram of tannic acid-imidazole / polyacrylamide composite hydrogel.
[0047] Fig.12 It is the infrared spectra of imidazole, tannic acid, and tannic acid-imidazole / polyacrylamide composite hydrogel. DETAILED DESCRIPTION
[0048] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0050] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0051] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0052] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0053] The invention discloses a preparation method and application of a tannic acid-imidazole / polyacrylamide composite hydrogel.
[0054] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0055] Embodiment 1:
[0056] Take 50mL of 6% tannic acid aqueous solution, dissolve it in an ice water bath for 1h according to the molar ratio of tannic acid to imidazole of 1:13, then add epichlorohydrin with the same molar number as imidazole, and continue to react for 1.5h to obtain a tannic acid-imidazole composite polymer; dissolve 0.4g of tannic acid-imidazole composite polymer in 20mL of deionized water, then add 7.5g of acrylamide monomer, stir well, add 0.3g of ammonium persulfate and 0.75N,N'-methylenebisacrylamide to the solution respectively, stir evenly to obtain a prepolymer solution, put the beaker containing the prepolymer solution into a 60℃ oven for 6h to prepare a tannic acid composite imidazole / polyacrylamide composite antibacterial hydrogel.
[0057] In the antibacterial performance test, the material showed significant antibacterial effects on Staphylococcus aureus and Escherichia coli, with the diameter of the antibacterial zone reaching 35.285 mm (see attached). Figure 1-2 In addition, the material also has good antioxidant properties, with a scavenging rate of 88.12% for DPPH free radicals and 81.68% for ABTS free radicals (see Appendix Figure 3-4 The microscopic morphology of the freeze-dried sample after the composite hydrogel absorbed water and balanced was a honeycomb structure, which was consistent with the characteristics of a hydrogel with high water absorption performance (see Appendix Figure 7 ).
[0058] Embodiment 2:
[0059] Referring to the preparation method of Example 1, the addition amount of tannic acid-imidazole composite polymer was modified to 0.1g, 0.2g, 0.3g and 0.5g respectively, and the antioxidant properties of tannic acid-imidazole / polyacrylamide hydrogel changed significantly, and the scavenging rates of DPPH free radicals were 78.09%, 87.54% and 82.15%; the scavenging rates of ABTS free radicals were 51.05%, 76.78%, 75.24% and 81.96%.
[0060] The polyacrylamide hydrogel used as a control had little scavenging effect on DPPH and ABTS free radicals.
[0061] Embodiment 3:
[0062] Using Example 1, the water absorption equilibrium swelling ratio of the prepared tannic acid-imidazole / polyacrylamide composite hydrogel after 24 hours was 607.65 times. Under the same conditions, the water absorption equilibrium swelling ratio of the polyacrylamide hydrogel was 696.41 times.
[0063] The water absorption equilibrium swelling ratios of the tannic acid-imidazole solution were changed to 0.1 g, 0.2 g, 0.3 g and 0.5 g, respectively, and were 544.04, 614.24, 684.75 and 702.69 times (see Appendix Figure 6 ).
[0064] Embodiment 4:
[0065] The tannic acid-imidazole / polyacrylamide composite hydrogel prepared in Example 1 was cut into a cuboid of fixed size (length 20 mm×10 mm×5 mm), and then a tensile test was performed on the sample at a speed of 100 mm / min using a universal testing machine tensile fixture. The sample did not break when the strain length was 22 mm, while the fracture length of the polyacrylamide gel was 1.40 mm; the gel strain was between 5.69 mm and 16.48 mm, and the shear force was about 4.59 N / mm 2 At this time, when the strain of polyacrylamide gel is 4.5 mm, the shear force reaches 1.92 N / mm 2 Under the conditions, the cross-linking density and network structure of the gel are significantly improved; at the same time, it has good adhesion to glass slides, rubber, stainless steel sheets, etc. (attached Figure 5 ).
[0066] Embodiment 5:
[0067] The compression modulus of the tannic acid-imidazole / polyacrylamide composite hydrogel prepared in Example 1 was measured, and the tensile test chart showed that the compression modulus of the composite hydrogel at different stretching rates was always higher than that of the polyacrylamide hydrogel, showing better anti-deformation ability.
[0068] Under the conditions of time and frequency changes, the storage modulus (G') and loss modulus (G") of the composite hydrogel are better than those of polyacrylamide hydrogel, demonstrating its superior energy storage and energy dissipation capabilities. Especially in the high frequency range, the G' of the composite hydrogel is significantly improved, indicating that it has higher stability and strength under rapid repeated loading (Appendix Figure 8-11 ).
[0069] Embodiment 6:
[0070] 0.1 g of tannic acid-imidazole composite polymer was dissolved in 20 mL of deionized water, and then the tannic acid-imidazole / polyacrylamide composite hydrogel prepared by the method of Example 1 was tested for antibacterial properties. Changing the amount of tannic acid added had a significant antibacterial effect on both Staphylococcus aureus and Escherichia coli.
[0071] When the concentration of tannic acid solution was 8%, 10% and 12%, the diameters of the inhibition zone against Staphylococcus aureus were 33.835mm, 31.775mm and 35.541mm respectively. In addition, the diameters of the inhibition zone against Escherichia coli were 19.095mm, 19.627mm and 19.767mm respectively.
[0072] Embodiment 7:
[0073] Referring to the preparation method of Example 1, the addition amount of tannic acid-imidazole composite polymer was modified to 0.1g, 0.2g, 0.3g and 0.5g, respectively. The tensile energy of tannic acid-imidazole / polyacrylamide hydrogel changed significantly, and the elongation at break was 6.012mm, 9.956mm, 8.520mm and ∞, respectively; the elongation at break of the polyacrylamide hydrogel as a control was only 1.406mm.
[0074] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a tannic acid-imidazole / polyacrylamide composite hydrogel, characterized in that: The method specifically comprises the following steps: (1) dissolving tannic acid in deionized water to obtain a tannic acid solution; (2) mixing the tannic acid solution with imidazole, stirring in an ice water bath, then adding epichlorohydrin dropwise, continuing the reaction, centrifuging and freeze-drying to obtain a tannic acid-imidazole composite polymer; (3) adding the tannic acid-imidazole composite polymer to the acrylamide solution, and then adding ammonium persulfate and N,N'-methylenebisacrylamide, and stirring evenly; (4) heating the reaction system of step (3) to initiate free radical polymerization, and preparing the tannic acid-imidazole / polyacrylamide composite hydrogel after a certain reaction time.
2. The method for preparing the tannic acid-imidazole / polyacrylamide composite hydrogel according to claim 1, characterized in that: The mass fraction of the tannic acid solution is 0.5% to 30%.
3. The method for preparing the tannic acid-imidazole / polyacrylamide composite hydrogel according to claim 1, characterized in that: The molar ratio of tannic acid to imidazole is 1:1 to 1:
20.
4. The method for preparing the tannic acid-imidazole / polyacrylamide composite hydrogel according to claim 1, characterized in that: The amount of acrylamide used is 5 mg to 15 g, the amount of ammonium persulfate used is 5 mg to 1 g, and the amount of N,N'-methylenebisacrylamide used is 5 mg to 1 g.
5. The method for preparing the tannic acid-imidazole / polyacrylamide composite hydrogel according to claim 1, characterized in that: 0.5-15 mL of epichlorohydrin is added to 50 mL of the mixture of tannic acid and imidazole, and the mixture of tannic acid and imidazole and epichlorohydrin continue to react in an ice water bath for 8-24 hours.
6. The method for preparing the tannic acid-imidazole / polyacrylamide composite hydrogel according to claim 1, characterized in that: The centrifugal speed in step (2) is 3000-10000 rpm, and the centrifugal time is 5 min to 1 h.
7. The method for preparing the tannic acid-imidazole / polyacrylamide composite hydrogel according to claim 1, characterized in that: The polymerization reaction temperature in step (4) is 20°C to 100°C, and the reaction time is 30min to 12h.
8. A tannic acid-imidazole / polyacrylamide composite hydrogel prepared by the method as claimed in claim 1.
9. Use of the tannic acid-imidazole / polyacrylamide composite hydrogel prepared by the method of claim 1 or the tannic acid-imidazole / polyacrylamide composite hydrogel as claimed in claim 8 in biomedicine, packaging and public health.
Citation Information
Patent Citations
Bacteriostatic antioxidant hydrogel with self-repairing function and preparation method thereof
CN114989345A
Rapidly-gelated conductive hydrogel as well as preparation method and application thereof
CN117510704A
Dual-network collagen-based supramolecular hydrogel and its preparation method
US20230331938A1